Semi-continuous extraction of palm kernel oil from palm kernels using supercritical carbon dioxide (SC-C02) with solvent recycling system. - Ab Kadir, Mohd Omar (Universiti Sains Malaysia, 2015)
Palm oil industry is known to be the most polluting industry in the country producing palm oil mill effluent (POME), requires large acreage of treatment system and polluting the environment. With SC-C02, the 25 steps can be achieved within the same mill thus reducing the transportation and energy cost moving from one mill to another.